ANALISIS KINERJA KEUANGAN PADA PT. ELNUSA TBK PERIODE 2013-2017 - Citra, Anggun Tiara (EKONOMIA, 2020)
Â The background of this research is that every company is required to improve its performance, The development of the company must always be evaluated in order to know the strengths and weaknesses of the company. This research aims to know and analyze the decrease in liquidity ratios based on current ratio, solvency ratios based on debt to equity ratio, profitability ratios based on return on assets, and activity ratios based on total assets turnover.This study aims to determine the decline in terms of liquidity ratios measured from Current Ratio, solvability ratios measured from Debt to Equity Ratio, profitability ratios measured from Return on Assets, and activity ratios measured from Total Assets Turnover from 2013 to 2017.The basic theory of this this research is that financial management which focuses on each of the liquidity ratios measured from the current ratio, solvability ratios measured from Debt to Equity Ratio, profitability ratios measured from Return on Assets and activity ratios measured from Total Assets Turnover.The ratio is measured from the Total Assets Turnover. The ratio is measured by the current ratio, the profitability ratio is measured from the current ratio. Data needed is 5 years, namely in 2013 to 2017 data obtained from the Indonesian stock exchangeThe results of the study showed: 1) the current ratio experienced an increase in 2013-2014, decreased in 2015, experienced an increase in 2016, and decreased in 2017. 2) the debt to equity ratio decreased in 2013-2014, experienced an increase in 2015, decreased in 2016, and experienced an increase in 2017. 3)the return on assets increase in 2013-2014 and decreased in 2015-2014. 4) the total assets turnover experienced an increase in 2013-2014 experienced a decline in 2015, and experienced an increase in 2016-2017.